Method for preparing road base material from incinerator slag and polluted sludge

By activating the incinerator slag and pretreating the polluted sludge, and carrying out hydrothermal reactions to prepare the road base material, the problems of environmental pollution and low resource utilization efficiency in the treatment of incinerator slag and polluted sludge are solved, and efficient and environmentally friendly harmless treatment and resource recycling are achieved.

CN119638359AActive Publication Date: 2025-03-18XINJIANG UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411669757.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing incinerator slag and polluted sludge treatment methods have problems such as environmental pollution risks, low resource utilization efficiency and complex processes, making it difficult to achieve harmless treatment and resource recycling.

Method used

By activating the incinerator slag and pretreating the contaminated sludge, mixing raw materials and carrying out hydrothermal reactions, mineralized materials are mixed with water glass solution, and the road base material is prepared.

Benefits of technology

This method effectively inhibits the generation of harmful particulate matter, reduces the mobility of heavy metals, enhances the strength, durability and compressive resistance of materials, and realizes the harmless treatment and efficient resource utilization of solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638359A_ABST
    Figure CN119638359A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a road base material by using incineration slag and polluted sludge, which comprises the following steps: carrying out wet tempering and chemical modification on the incineration slag to obtain activated incineration slag; treating the solid-phase sludge by using low-temperature plasma to obtain pretreated sludge; uniformly mixing the activated incineration slag and the pretreated sludge to obtain a mixed raw material; adding a mineralizer into the mixed raw material, uniformly mixing, and adding water to obtain a reaction wet material; performing hydrothermal reaction on the reaction wet material to obtain a mineralized material; and uniformly mixing the mineralized material with the water glass solution to obtain the road base material. According to the method, heavy metals in the incineration slag and the polluted sludge are promoted to react with the mineralizing agent under the hydrothermal treatment condition, so that the heavy metals are solidified and stabilized, and the long-term leaching risk of the heavy metals in the roadbed and the mobility of the heavy metals in the environment are effectively reduced. Meanwhile, a thermodynamically stable mineral phase is generated by hydrothermal treatment, so that the strength, durability and compression resistance of the roadbed material are remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of harmless treatment of solid waste and environmental protection, and in particular to a method for preparing road base material by using incineration slag and polluted sludge. Background Art

[0002] In the field of harmless treatment of solid waste and environmental protection technology, the treatment of incineration slag and contaminated sludge has always been a difficult and hot issue. As the residue in the incineration process, incineration slag is rich in heavy metals and other harmful substances. If it is not properly treated, it is very easy to cause secondary pollution to the ecological environment. Similarly, contaminated sludge, especially sludge from industrial sewage treatment plants and urban sewage treatment plants, contains a large amount of toxic and harmful heavy metals and organic pollutants. If it is directly discharged or improperly treated, it will pose a serious threat to soil, water bodies and groundwater.

[0003] Traditional methods for treating incineration slag and contaminated sludge mainly include landfill, solidification / stabilization and heavy metal recovery. Although the landfill method has relatively low cost, it has problems such as large land occupation and high risk of leakage, which is not conducive to environmental protection and sustainable development. Solidification / stabilization technology stabilizes or seals harmful substances in materials through physical or chemical means. Although it reduces the risk to a certain extent, under certain environmental conditions, such as acidic or reducing environments, harmful substances such as heavy metals may still be released again, posing potential environmental risks.

[0004] In addition, existing heavy metal recovery technologies, such as thermal treatment, electrochemical methods, chemical extraction and biotechnology, although theoretically can achieve the recycling of heavy metals, generally face problems such as high cost, high energy consumption and complex processes. In practical applications, they are less efficient and may bring the risk of secondary pollution, which limits their widespread application. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the present invention provides an efficient and environmentally friendly method for treating incineration slag and contaminated sludge, which can achieve both harmless treatment and effective recycling of resources.

[0006] A method for preparing road base material by using incineration slag and polluted sludge, comprising the following steps:

[0007] S1: Activating the incineration slag, subjecting the incineration slag to wet conditioning and chemical modification to obtain activated incineration slag;

[0008] S2: pre-treating the polluted sludge, separating the polluted sludge into solid and liquid to obtain solid-phase sludge, and subjecting the solid-phase sludge to low-temperature plasma treatment to obtain pre-treated sludge;

[0009] S3: preparing a mixed raw material, mixing the activated incineration slag and the pretreated sludge evenly to obtain a mixed raw material;

[0010] S4: preparing a reaction wet material, adding a mineralizer to the mixed raw material and mixing evenly to obtain a reaction dry material, and adding water to the reaction dry material to obtain a reaction wet material;

[0011] S5: preparing a mineralized material through a hydrothermal reaction, placing the reaction wet material in a hydrothermal reactor for a hydrothermal reaction to obtain a mineralized material;

[0012] S6: preparing a road base material, mixing the mineralized material and the water glass solution evenly to obtain a road base material.

[0013] Furthermore, the particle size of the incineration slag is ≤200 μm.

[0014] Furthermore, the chemical modification method is to mix the wet-modulated incineration slag with the water glass solution evenly and then let it react for 4 to 12 hours. The wet modulation method is to add 10 to 15% of water by dry weight to the incineration slag. The modulus of the water glass solution is 2.0 to 3.3, the concentration is 20 to 30%, and the amount added is 5 to 10 times the mass of the wet-modulated incineration slag.

[0015] Furthermore, the solid-liquid separation is performed using a centrifugal separation device, the rotation speed of the centrifugal separation device is 3000-4500 rpm / min, the time is 10-20 min, and the water content of the solid phase sludge is 20-30%.

[0016] Furthermore, the low-temperature plasma treatment temperature is 20-30° C., the discharge voltage is 25-35 kV, and the treatment time is 30-45 min.

[0017] Furthermore, the mass fraction of the activated incineration slag in the mixed raw material is 60-80%, and the mass fraction of the pre-treated sludge is 20-40%.

[0018] Furthermore, the mineralizer consists of calcium silicate and calcium hydrogen phosphate, with mass fractions of 70-80% and 20-30% respectively.

[0019] Furthermore, the amount of the mineralizer added to the reaction dry material is 5-15% of the mass of the mixed raw material, and the amount of water added to the reaction dry material is 32-42% of the weight of the reaction dry material.

[0020] Furthermore, the hydrothermal reaction temperature is 180-250° C., the reaction pressure is 3-5 MPa, and the reaction time is 6-12 h.

[0021] Furthermore, the modulus of the water glass solution is 2.0-2.5, the concentration is 40-50%, and the mass fractions of the mineralized material and the water glass solution are 80-90% and 10-20%, respectively.

[0022] In summary, the present invention has the following beneficial effects:

[0023] First, the present invention uses a sealed reactor to carry out hydrothermal mineralization reaction, which can effectively inhibit the generation of harmful particles, thereby significantly reducing the pollution to the environment caused by the material processing process. At the same time, the process promotes the formation of thermodynamically stable mineral phases, greatly enhancing the strength, durability and compressive resistance of the road base material.

[0024] Second, the present invention promotes the chemical reaction between heavy metals and mineralizers to form stable compounds, significantly reducing the mobility of heavy metals and enhancing the stability of the solidified body after treatment. This method solves the environmental pollution problems caused by incineration slag and contaminated sludge, effectively avoids the risk of secondary pollution, and significantly improves the engineering performance of materials, achieving harmless treatment of solid waste and efficient resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 The present invention provides a flow chart of a method for preparing road base material by using incineration slag and polluted sludge. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] A method for preparing road base material using incineration slag and polluted sludge, such as Figure 1 As shown, the following steps are included:

[0029] S1: preparing activated incineration slag, screening, wet conditioning, chemically modifying, stirring, drying and grinding the incineration slag to obtain activated incineration slag;

[0030] S2: preparing pretreated sludge, separating the polluted sludge into solid and liquid by a centrifugal separation device to obtain solid-phase sludge, then placing the solid-phase sludge in a low-temperature plasma reactor for treatment, and then drying and grinding the plasma-treated sludge to obtain pretreated sludge;

[0031] S3: preparing a mixed raw material, mixing the activated incineration slag and the pre-treated sludge in proportion to obtain a mixed raw material;

[0032] S4: preparing a reaction wet material, mixing calcium silicate powder and calcium hydrogen phosphate powder in proportion to obtain a mineralizer, mixing the mixed raw material and the mineralizer to obtain a reaction dry material, and adding an appropriate amount of water to obtain a reaction wet material;

[0033] S5: preparing a mineralized material through a hydrothermal reaction, placing the wet reaction material in a hydrothermal reactor, adjusting appropriate reaction temperature, reaction pressure and treatment time to perform a hydrothermal reaction, and then drying and grinding the product to obtain a mineralized material;

[0034] S6: preparing a road base material, mixing the mineralized material and the water glass solution in a uniform proportion to prepare a road base material.

[0035] This solution treats pollutants such as incinerator slag and contaminated sludge through hydrothermal reaction, promotes the formation of thermodynamically stable mineral phases, greatly enhances the strength, durability and compressive resistance of the road base material, and promotes the chemical reaction between heavy metals in the pollutants and mineralizers in the process to form stable compounds, significantly reducing the mobility of heavy metals and enhancing the stability of the solidified body after treatment. This solution solves the environmental pollution problems caused by incinerator slag and contaminated sludge, effectively avoids the risk of secondary pollution, and significantly improves the engineering performance of the material, achieving harmless treatment of solid waste and efficient resource utilization.

[0036] Furthermore, the method for preparing activated incineration slag in step S1 comprises:

[0037] The screening method is to screen the incineration slag to remove particles and impurities with a particle size greater than 200 μm, so as to obtain fine-particle incineration slag with uniform particle size.

[0038] The wet preparation method is to add 10-15% of water by dry weight into the incineration slag to make its physical and chemical properties uniform and reduce dust generation.

[0039] The chemical modification method comprises mixing the incineration slag and the water glass solution uniformly and then standing the mixture to react for 4 to 12 hours. The modulus of the water glass solution is 2.0 to 3.3, the concentration is 20 to 30%, and the amount added is 5 to 10 times the mass of the incineration slag. The water glass solution can react with the metal oxides in the incineration slag to generate a silicate mineral phase, thereby activating the potential active substances in the incineration slag and improving its reaction activity.

[0040] The stirring method is mechanical stirring, the drying condition is drying at 100° C. for 24 hours, and the grinding time is 8 to 15 minutes. The above operation can increase the specific surface area of ​​the material, enhance its ability to combine with other components in the subsequent reaction process, and thus promote the mineralization reaction.

[0041] Furthermore, the method for preparing the pretreated sludge in step S2 comprises:

[0042] The solid-liquid separation is carried out by a centrifugal separation device, the rotation speed of the centrifugal separation device is 3000-4500 rpm / min, the time is 10-20 min, and the water content of the solid phase sludge is 20-30%.

[0043] The solid phase sludge is treated by a low-temperature plasma reactor, the working chamber volume of the low-temperature plasma reactor is 10-20L; a cooling water circulation system is equipped, and the treatment temperature of the low-temperature plasma is controlled at 20-30°C. Since the working temperature range of the low-temperature plasma reactor is from hundreds of degrees Celsius to thousands of degrees Celsius, and the electron temperature is from thousands to tens of thousands of degrees Celsius; the contact time between the plasma and the treated material is from a few microseconds to hundreds of microseconds, and the treatment temperature of the low-temperature plasma refers to the external environment temperature, which is maintained within the range of normal temperature (about 20-30°C) to ensure the stability of the low-temperature environment; the reactor adopts a bipolar pulse power supply, The operating frequency is controlled at 25-35kHz, and the discharge voltage is 25-35kV, so as to ensure the stable generation of plasma and effectively control the energy coupling efficiency in the reaction process to improve the generation efficiency of plasma. A high-efficiency ceramic dielectric barrier layer is arranged inside the reactor to further optimize the generation of plasma. The solid phase sludge is treated with the low-temperature plasma reactor for 30-45min. Under the action of the low-temperature plasma, the organic pollutants in the sludge are decomposed through physical bombardment and chemical reaction. Meanwhile, the ultraviolet photons in the low-temperature plasma effectively inactivate the pathogenic microorganisms in the sludge and reduce the biological toxicity of the sludge.

[0044] The sludge treated by the low-temperature plasma reactor is placed in a drying device and dried at 100° C. for 24 hours, and then the dried sludge is ground by a grinding device for 10 to 15 minutes.

[0045] Furthermore, the method for preparing the mixed raw material in step S3 includes:

[0046] The mass fraction of the activated incineration slag in the mixed raw material is 60-80%, and the mass fraction of the pre-treated sludge is 20-30%.

[0047] Furthermore, the method for preparing the reaction wet material in step S4 comprises:

[0048] The mineralizer is composed of calcium silicate and calcium hydrogen phosphate, with mass fractions of 70-80% and 20-30% respectively. Among them, calcium silicate can react with silicon and calcium components in the material under hydrothermal reaction conditions to generate stable silicate mineral phases such as tobermorite, significantly improving the mechanical properties and durability of the mineralized product; calcium hydrogen phosphate can react with metal ions in the material to generate insoluble phosphate precipitation, fix harmful heavy metals, further improve the chemical stability of the material, and reduce the risk of leaching of harmful substances.

[0049] The amount of the mineralizer added to the reaction dry material is 5-15% of the mass of the mixed raw material.

[0050] The amount of water added to the reaction dry material is 32-42% of the weight of the reaction dry material, ensuring that the water is in full contact with the reaction dry material.

[0051] Furthermore, the method for preparing the mineralized material by hydrothermal reaction in step S5 includes:

[0052] The hydrothermal reactor is equipped with an adjustable speed stirring device to ensure that the materials are evenly distributed under high temperature and high pressure to prevent agglomeration and local insufficient reaction; the reactor adopts a double-layer jacket design, and the outer jacket is equipped with an electric heating or steam heating system to control the reaction temperature. The temperature sensor is connected to the control system to monitor and adjust the reaction temperature in real time; the inner layer is a high-pressure structure, and the pressure is monitored by a pressure sensor, and the required pressure is maintained by heating and the vapor pressure of the liquid in the reactor. This scheme uses a sealed reactor for hydrothermal mineralization reaction, which can effectively inhibit the generation of harmful particulate matter and significantly reduce the pollution to the environment during material processing.

[0053] The hydrothermal reactor controls the reaction temperature at 180-250° C. and maintains the pressure at 3-5 MPa. The entire hydrothermal reaction process lasts for 6-12 hours to ensure that the harmful substances in the incineration slag and the polluted sludge fully react chemically with the mineralizer to generate thermodynamically stable silicate and phosphate mineral phases.

[0054] The temperature of the hydrothermal reaction product is gradually reduced to room temperature through the cooling system of the hydrothermal reactor, and then the internal pressure is slowly released; although the hydrothermal reactor operates under high temperature conditions, since the reaction is carried out in a high-pressure environment, the product after the reaction may still retain a certain amount of moisture. The reaction product is taken out, dried at a temperature of 80 to 100° C. for 24 hours to completely remove the residual moisture, and then ground for 8 to 12 minutes.

[0055] Furthermore, the method for preparing the road base material in step S6 includes:

[0056] The modulus of the water glass solution is 2.0-2.5, the concentration is 40-50%, and the mass fractions of the mineralized material and the water glass solution are 80-90% and 10-20% respectively.

[0057] The specific implementation process is to use the road base material prepared by the present invention to carry out roadbed compaction, and the process includes key steps such as roadbed compaction and maintenance.

[0058] The compaction method adopts a progressive compaction method, using a steel wheel roller with a weight range of 18 to 22 tons to roll the mixed material in layers, with the thickness of each layer controlled within 150 mm, until the designed compaction requirement is reached; during rolling, two low-speed static compactions are first performed at a speed of about 1.0 to 1.4 km / h to eliminate initial voids in the material and achieve initial density and uniformity; then two medium-speed static compactions are performed at a speed of 1.8 to 2.2 km / h to further improve the density and uniformity of the material; then two strong vibration compactions are performed at a speed of 2.5 to 3.0 km / h, with the amplitude controlled at 1.5 to 2.0 m m, the vibration frequency is controlled at 30-35Hz, and the particle arrangement is optimized and the internal voids are reduced through larger amplitude and higher frequency; then two weak vibration compactions are carried out at a speed of 2.3-2.7km / h, the amplitude is controlled at 0.8-1.2mm, and the frequency is controlled at 20-25Hz, so as to alleviate the stress concentration that may be caused by strong vibration and enhance the overall stability of the material; finally, a static pressure finishing is carried out at a speed of about 2.0-2.4km / h to make the surface smoother and further improve the density and smoothness; through the synergistic effect of this series of steps, the overall density, uniformity and stability of the material are ensured.

[0059] The curing method is wet curing, and the relative humidity during the curing process is not less than 90%. The curing time is adjusted to 7 to 14 days according to the temperature changes of the seasons to ensure sufficient hydration reaction of the material.

[0060] Example 1

[0061] This embodiment provides a method for preparing a road base material using incineration slag and contaminated sludge, comprising the following steps:

[0062] S1: The incineration slag is taken from the incineration residue of a domestic waste incineration plant, which mainly contains heavy metal elements lead (Pb) and cadmium (Cd). The above heavy metal elements are enriched in the slag, which has potential environmental pollution and biological toxicity risks.

[0063] The incineration slag with a particle size of less than 200 μm is mixed with 12% of water by dry weight and tempered to a uniform state. Subsequently, the tempered incineration slag is mixed with 8% of a water glass solution by mass of the incineration slag, wherein the modulus of the water glass is 2.5 and the concentration is 25%. The mixture is fully stirred and allowed to stand for reaction for 10 hours, and then dried, and the resulting material is ground for 10 minutes to obtain activated incineration slag.

[0064] S2: The contaminated sludge was taken from the wastewater treatment system of an electroplating plant. The sludge has a high risk of environmental pollution. The plating solution used in the electroplating process contains heavy metal elements chromium (Cr), nickel (Ni) and zinc (Zn). The above heavy metal elements accumulate in excess in the environment, which may cause allergenicity, toxicity, and even carcinogenicity to ecosystems and organisms.

[0065] The solid sludge with a water content of about 25% obtained by centrifugal separation is placed in a low-temperature plasma reactor for treatment. The temperature in the reactor is controlled at 25±2°C, the operating frequency is set to 30kHz, the discharge voltage is 30kV, and the treatment time is 40min. Subsequently, the plasma-treated sludge is dried and ground to obtain pre-treated sludge.

[0066] S3: The activated incineration slag and the pre-treated sludge are mixed uniformly in proportion to form a mixed raw material, wherein the mass fraction of the activated incineration slag is 60% and the mass fraction of the pre-treated sludge is 40%.

[0067] S4: Calcium silicate powder and calcium hydrogen phosphate powder are mixed uniformly in proportion to form a mineralizer, wherein the mass fraction of calcium silicate powder is 70% and the mass fraction of calcium hydrogen phosphate powder is 30%. The mineralizer accounting for 8% of the mass of the mixed raw materials is added to the mixed raw materials, and the mixture is fully mixed to obtain a dry reaction material. Subsequently, water accounting for 35% of the total mass of the dry reaction material is added to the dry reaction material, and the mixture is further mixed to obtain a wet reaction material.

[0068] S5: The wet reaction material is placed under hydrothermal reaction conditions for treatment, the reaction temperature is controlled at 200°C, the reaction pressure is set to 4MPa, and the treatment time is 10h. Subsequently, the product obtained by the hydrothermal reaction is dried and ground for 10min to obtain a mineralized material.

[0069] S6: The mineralized material is mixed evenly with a water glass solution having a modulus of 2.5 and a concentration of 40% in a certain proportion, wherein the mass fraction of the mineralized material is 80% and the mass fraction of the water glass solution is 20%.

[0070] The designed road base area is 50m2, the top surface width is 2.5m, the designed thickness is 25cm, and a 20-ton steel wheel roller is used for two-layer paving. The rolling process includes the following steps: first, two low-speed static compaction at a speed of about 1.2km / h; then, two medium-speed static compaction at a speed of 2.0km / h; then, two strong vibration compaction at a speed of 2.8km / h, with the amplitude controlled at 1.8mm and the vibration frequency controlled at 32Hz; then, two weak vibration compaction at a speed of 2.5km / h, with the amplitude controlled at 1.0mm and the vibration frequency controlled at 22Hz; finally, one static compaction at a speed of about 2.2km / h to finish the surface.

[0071] The maintenance is carried out by covering with moisturizing sacks. The overlap width between adjacent sacks is not less than 10cm, and a layer of soil is covered on the outside of the sacks. The covered sacks are buried with soil around them, and water is sprinkled regularly to ensure that the relative humidity of the sacks and the covering soil is maintained at 95%. After 7 days of maintenance, the road base materials are sampled and tested.

[0072] Example 2

[0073] The only difference from Example 1 is that in step S3 of this embodiment, the mass fractions of activated slag and pre-treated sludge contained in the mixed raw material are 80% and 20% respectively.

[0074] Example 3

[0075] The only difference from Example 1 is that in step S4 of this embodiment, the amount of the mineralizer added accounts for 12% of the mass of the mixed raw material.

[0076] Comparative Example 1

[0077] The only difference from Example 1 is that in step S5 of this comparative example, the reaction temperature is set to 25°C (room temperature) and the reaction pressure is set to 101 KPa (normal pressure), that is, the reaction of the wet material is carried out under normal temperature and pressure conditions.

[0078] Test results and analysis

[0079] The original samples taken in each embodiment were tested for CBR bearing capacity according to the "Highway Roadbed Design Code" (JTG D30-2015), the unconfined compressive strength was tested according to the "Standard for Geotechnical Test Methods" (GB / T 50123-2019), the anti-dry-wet cycle performance and anti-freeze-thaw cycle performance were tested according to the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG E51-2009), and the solid waste leaching toxicity was tested according to the "Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid Nitric Acid Method" (HJ / T299-2007). The results are shown in Table 1.

[0080] Table 1 Summary of road base material properties prepared in various embodiments

[0081]

[0082] According to the "Highway Roadbed Design Specification" (JTG D30-2015), the CBR load ratio requirement of the subbase material is usually not less than 30%, while the requirement of the upper base material is not less than 50%. Among them, the CBR load ratio of the highway road base material should reach or exceed 60% to ensure that it is sufficient to cope with the heavy load of high-speed traffic. According to the test results in the embodiments of the present invention, the CBR load ratios are 60%, 65% and 62%, respectively, which are in line with the relevant specifications and are suitable for road structures that bear large loads.

[0083] As an important indicator for evaluating the bearing capacity of materials under compression, the unconfined compressive strength of the subbase is usually required to be no less than 1.5MPa, and that of the upper base is required to be no less than 2.5MPa. In the embodiment of the present invention, the unconfined compressive strengths obtained by testing are 4.0MPa, 4.2MPa and 4.1MPa, respectively, far exceeding the strength requirements of the subbase and upper base.

[0084] According to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG E51-2009), the strength loss rate of the material shall not exceed 15% after 10 dry-wet cycles; and the strength loss rate shall not exceed 5% after 5 freeze-thaw cycles, so as to ensure that the material can maintain structural stability and durability under humidity and temperature changes. After testing, the strength loss rates of the road base material in the embodiment of the present invention after 10 dry-wet cycles were 8%, 6% and 7%, respectively, which are far lower than the requirements of the specification, showing excellent resistance to dry-wet cycles, and suitable for use in rainy areas or areas with frequent humidity fluctuations.

[0085] In addition, the strength loss rates of the materials in the embodiments of the present invention after 5 freeze-thaw cycles were 1.5%, 1% and 1.2%, respectively, which were significantly better than the standard requirements, showing extremely strong freeze-thaw resistance, suitable for cold areas, and able to maintain the stability of structure and performance in long-term freeze-thaw environments. The results of the analysis of the mechanical properties and durability of the road base materials in the embodiments of the present invention show that the road base materials of the present invention are suitable for a variety of road base structures, including high-grade road bases such as expressways and general roads that have high requirements for bearing capacity and long-term durability.

[0086] According to the "Identification of Hazardous Waste Leaching Toxicity" (GB 5085.3-2007), the leaching toxicity limits of heavy metals are: the limit of lead Pb is 5.0mg / L, the limit of cadmium Cd is 1.0mg / L, and the limit of hexavalent chromium Cr is 1.0mg / L. 6+ The limit value of is 5.0 mg / L, the limit value of nickel Ni is 5.0 mg / L, and the limit value of zinc Zn is 100 mg / L. The leaching data of heavy metals obtained in the embodiments of the present invention are all lower than the limits specified in the standards. Therefore, the embodiments of the present invention are all within the safe range in terms of heavy metal leaching toxicity and meet the relevant requirements of environmental protection laws and regulations.

[0087] In summary, the road base materials in all embodiments provided by the present invention show significant advantages in mechanical properties, which are specifically reflected in higher CBR bearing capacity and unconfined compressive strength, ensuring that they can maintain superior bearing capacity and structural stability under different load conditions. In terms of durability, the material shows excellent resistance to dry-wet cycles and freeze-thaw cycles, can maintain its stable performance under harsh climatic conditions, and significantly reduce material degradation and damage caused by environmental changes. At the same time, the road base material of the present invention has an excellent heavy metal stabilization effect, can effectively solidify heavy metals, and meets the requirements of relevant environmental protection standards, thereby effectively reducing the potential pollution risk to the surrounding ecological environment.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing road base material using incineration slag and polluted sludge, characterized in that: The following steps are involved: S1: Activating the incineration slag, subjecting the incineration slag to wet conditioning and chemical modification to obtain activated incineration slag; S2: pre-treating the polluted sludge, separating the polluted sludge into solid and liquid to obtain solid-phase sludge, and subjecting the solid-phase sludge to low-temperature plasma treatment to obtain pre-treated sludge; S3: preparing a mixed raw material, mixing the activated incineration slag and the pretreated sludge evenly to obtain a mixed raw material; S4: preparing a reaction wet material, adding a mineralizer to the mixed raw material and mixing evenly to obtain a reaction dry material, and adding water to the reaction dry material to obtain a reaction wet material; S5: preparing a mineralized material through a hydrothermal reaction, placing the reaction wet material in a hydrothermal reactor for a hydrothermal reaction to obtain a mineralized material; S6: preparing a road base material, mixing the mineralized material and the water glass solution evenly to obtain a road base material.

2. The method for preparing road base material using incineration slag and polluted sludge according to claim 1, characterized in that: The particle size of the incineration slag is ≤200 μm.

3. The method for preparing road base material using incineration slag and polluted sludge according to claim 1, characterized in that: The chemical modification method comprises mixing the wet-modulated incineration slag with a water glass solution evenly and then allowing the mixture to react for 4 to 12 hours. The wet-modulation method comprises adding 10 to 15% of water by dry weight to the incineration slag. The modulus of the water glass solution is 2.0 to 3.3, the concentration is 20 to 30%, and the amount added is 5 to 10 times the mass of the wet-modulated incineration slag.

4. The method for preparing road base material using incineration slag and polluted sludge according to claim 1, characterized in that: The solid-liquid separation is carried out by a centrifugal separation device, the rotation speed of the centrifugal separation device is 3000-4500 rpm / min, the time is 10-20 min, and the water content of the solid phase sludge is 20-30%.

5. The method for preparing road base material by using incineration slag and polluted sludge according to claim 1, characterized in that: The low-temperature plasma treatment temperature is 20-30° C., the discharge voltage is 25-35 kV, and the treatment time is 30-45 min.

6. The method for preparing road base material by using incineration slag and polluted sludge according to claim 1, characterized in that: The mass fraction of the activated incineration slag in the mixed raw material is 60-80%, and the mass fraction of the pre-treated sludge is 20-40%.

7. The method for preparing road base material using incineration slag and polluted sludge according to claim 1, characterized in that: The mineralizer consists of calcium silicate and calcium hydrogen phosphate, with mass fractions of 70-80% and 20-30% respectively.

8. The method for preparing road base material by using incineration slag and polluted sludge according to claim 1, characterized in that: The amount of the mineralizer added to the reaction dry material is 5-15% of the mass of the mixed raw material, and the amount of water added to the reaction dry material is 32-42% of the weight of the reaction dry material.

9. The method for preparing road base material using incineration slag and polluted sludge according to claim 1, characterized in that: The hydrothermal reaction temperature is 180-250° C., the reaction pressure is 3-5 MPa, and the reaction time is 6-12 hours.

10. The method for preparing road base material by using incineration slag and polluted sludge according to claim 1, characterized in that: The modulus of the water glass solution is 2.0-2.5, the concentration is 40-50%, and the mass fractions of the mineralized material and the water glass solution are 80-90% and 10-20% respectively.

Citation Information

Patent Citations

  • Method for treating fly sh by sludge

    CN106424077A

  • Method for separating and recovering multiple cation heavy metals in water through phase-transition regulation and control

    CN107381705A

  • Cooperative treatment method and system for waste incineration fly ash and silicon-rich waste

    CN116283094A

  • Sludge treatment method

    CN117510007A

  • Production of solidified body from fly ash of rubbish incinerator

    JP2000308867A